How the financial crisis and great recession affected higher education - Brown, Jeffrey R. (Jeffrey Robert), 1968-; Hoxby, Caroline Minter (National Bureau of Economic Research conference report., 2014)
The recent financial crisis had a profound effect on both public and private universities, which faced shrinking endowments, declining charitable contributions, and reductions in government support. Universities responded to these stresses in different ways. This volume presents new evidence on the nature of these responses, and on how the incentives and constraints facing different institutions affected their behavior. The studies in this volume explore how various practices at institutions of higher education, such as the drawdown of endowment resources, the awarding of financial aid, and spending on research, responded to the financial crisis. The studies examine universities as economic organizations that operate in a complex institutional and financial environment. The authors examine the role of endowments in university finances and the interaction of spending policies, asset allocation strategies, and investment opportunities. They demonstrate that universities behavior can be modeled using economic principles.